2019
DOI: 10.1186/s12978-019-0671-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the maternal deaths surveillance and response system at the health district level in Guinea in 2017 through digital communication tools

Abstract: BackgroundReducing maternal mortality still remains a major challenge in low-income countries. This study aims to explore how digital communication tools can be used to evaluate the maternal deaths surveillance and response (MDSR) system at the health district level in Guinea.MethodsA descriptive cross-sectional study was conducted, using an innovative digital approach called District.Team, from April to September 2017. This study targeted all 38 district medical officers in Guinea. In addition to district med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 12 publications
1
25
3
Order By: Relevance
“…However; in this study only 55 (65.5%) and 8 (0.6%) of maternal and perinatal deaths were reviewed respectively. This finding (the maternal part) is higher than other studies from Kenya and Guinea that reported review of half of maternal deaths [34, 35]. In contrast, this finding is lower compared to the national target of 90% [31] and the finding from Uganda which reported review of 71% of maternal death and 33.3% of perinatal deaths [36].…”
Section: Discussionmentioning
confidence: 55%
“…However; in this study only 55 (65.5%) and 8 (0.6%) of maternal and perinatal deaths were reviewed respectively. This finding (the maternal part) is higher than other studies from Kenya and Guinea that reported review of half of maternal deaths [34, 35]. In contrast, this finding is lower compared to the national target of 90% [31] and the finding from Uganda which reported review of 71% of maternal death and 33.3% of perinatal deaths [36].…”
Section: Discussionmentioning
confidence: 55%
“…Some key principles of the start-up industry were introduced4: such as putting one’s focus on just a few hypotheses, using a simplified digital solution to test them, introduce active monitoring and rapid identification and adoption of emerging lessons. The collective intelligence strategy applied to ‘hard data’—tested under district.team—proved to be particularly effective14 and popular among district managers. At the same time, it did also highlight that transforming health administrations into LO necessitates proper time and commitment 15…”
Section: Our Practice In Collective Learningmentioning
confidence: 99%
“…Moreover, examining the viewpoint of health workers about the maternal mortality system, other studies have had a positive attitude towards this system, and considered its flexibility, acceptability and sensitivity to be valuable [ 17 , 18 ]. However, other studies have referred to underreporting of maternal deaths [ 1 ], failure to obtain the real causes of deaths, and the effect of health barriers on the system [ 7 , 19 , 20 ]. These studies have emphasized the need to modify surveillance system processes based on resolving structural problems and sensitizing health practitioners so that this system can be used as optimally as possible.…”
Section: Discussionmentioning
confidence: 99%